(untitled) (Research, Society and Development, 2024)
Objective: To quantitatively and spatially analyze the epidemiological characteristics of spina bifida from January 2013 to December 2023. Methodology: This is an epidemiological study, with a descriptive and quantitative nature on the epidemiological characteristics of spina bifida in Brazil, carried out based on data from the health information department of the SUS (Unified Health System). The variables used were: hospital admissions, mortality rate, deaths, age group, color/race, sex, type of care and health macro-region. Furthermore, such data from the SUS health information system were crossed with research information collected from reading articles linked to Scielo and Pubmed. Results: In the studies, 11,530 cases of spina bifida were observed in Brazil between 2013 and 2023. The Northeast region was responsible for 4,804 cases, followed by the Southeast region with 3,694 cases. Regarding the number of hospitalizations per year, it can be concluded that 2015 had 1,205 hospitalizations, followed by 2016 with 1,175. According to age group, the number of hospitalizations in children under 1 year old was 7,880. White and female individuals were the most affected. Conclusion: The Northeast was the state with the highest number of hospitalizations, as well as the year 2015, with the year with the lowest number of hospitalizations being 2013. The age group most affected were those under 1 year of age. From this perspective, spina bifida is seen as a serious public health problem.